Reviewing the Contributors towards the Performance of the New Islamic Supply Chain Model - Adam Mohd Saifudin; Nizamuddin Zainuddin; Ezanee Mohamed Elias; Siti Nur Fatehah Shamsuddin; Azim Azuan Osman (International Journal of Supply Chain Management, 2018)
This is a conceptual paper on the contributing factors of the performance of the new Islamic supply chain model in Malaysia. There are several contributors toward the model that has been reviewed. They are:- 1) Halal Traceability and Tracking Activity, 2) Halal Certification and Labelling Process, 3) Halal Facilities Segregation and 4). Halal Food Quality Management. All these contributors will be considered in developing new Islamic supply chain management model in Malaysia using robust econometric regression. Keywords New Islamic supply chain model, Halal Traceability, Tracking Activity, Halal Certification, Labelling Process, Halal Facilities Segregation and Halal Food Quality Management.